TRANSPARÊNCIA ATIVA NO IFTO: UM OLHAR SOBRE A LINGUAGEM E ACESSIBILIDADE DAS INFORMAÇÕES FINANCEIRAS (REMUNOM, 2024)
The Federal Constitution of 1988 guarantees the fundamental right of access to information, assigning the State the responsibility of ensuring transparency in public actions. Regulations such as the Fiscal Responsibility Law, the Transparency Law, and the Access to Information Law have strengthened this right, fostering clearer interaction between the public and government officials. With technological advancements, there is an opportunity for the government to enhance communication and societal engagement, but often official communications use overly technical language, making it difficult for citizens to understand and exercise social control. In this context, the objective of this research is to investigate how the Federal Institute of Tocantins (IFTO) complies with the legal requirements for active transparency regarding its financial and budgetary information, as well as applying the principles of plain language. The approach used is qualitative and exploratory, based on bibliographic and documentary research, with data primarily collected through a systematic analysis of the institution’s official portal. The results indicate that IFTO largely meets the requirements for active transparency, but still needs adjustments to make the language used in budget and financial execution reports more accessible.